Posttraumatic Soft Tissue Defects of the Heel: Comparison of Reconstructive Options and Results - Roy, Satyaki; Asokan, Harin; John, Jerry R.; Rastogi, Ashu; Tripathy, Satyaswarup; Gaba, Sunil; Sharma, Ramesh K. (Indian Journal of Plastic Surgery, 2025)
The heel is difficult to reconstruct if it is avulsed off following accidents. Heelpad avulsion may be suprafascial or subfascial. Reconstructive options include skin grafts and flaps, depending on the involvement of weight-bearing area and exposed bone. We describe a series of patients who underwent heel pad reconstruction.Patients were grouped into two, depending on flap or graft reconstruction. The number of operations, time taken for recovery, complications, revision surgery, sensations, and footwear use were analyzed. Dynamic pedogram analysis was performed to assess heel pressures.Twenty-one patients were assessed, out of which flap reconstruction was performed in 12. Nineteen patients achieved full weight bearing. Seventeen patients required revision procedures such as flap thinning. The mean time to walk, in the flap group was 14.3 weeks (range: 10–20 weeks) while that in the graft group was 11.5 weeks (range: 6–16 weeks). There was no difference in the reinnervation when comparing presence of light touch (p = 0.49) and pain (p = 0.37) between the two groups. On pedogram analysis, the mean peak pressures in the graft group were significantly less when compared with normal foot (p = 0.017). The mean peak pressures were comparable in both involved and uninvolved feet, among patients who underwent flap reconstruction.Skin grafts demonstrated good stability even in the absence of customized footwear. A flap procedure can be avoided for suprafascial avulsions. The level of protective sensation achieved by spontaneous reinnervation seems to be sufficient for maintaining a functional well-healed foot.
Keywords: heel pad avulsion; skin grafts; fasciocutaneous flaps; weight-bearing; reconstructive surgery; dynamic pedogram analysis; protective sensation; suprafascial versus subfascial; revision procedures; foot pressure distribution